Dosimetric advantages afforded by a new irradiation technique, Dynamic WaveArc, used for accelerated partial breast irradiation. (April 2018) - Ono, Yuka; Yoshimura, Michio; Hirata, Kimiko; Ono, Tomohiro; Hirashima, Hideaki; Mukumoto, Nobutaka; Nakamura, Mitsuhiro; Inoue, Minoru; Hiraoka, Masahiro; Mizowaki, Takashi
Highlights: Dosimetric advantages of DWA for APBI was proposed. Patient-specific dosimetric quality assurance of DWA was confirmed. The dose distributions of DWA, 3DCRT and VMAT were compared. DWA for APBI reduced the dose to the organs at risk, especially to the heart. Abstract: Purpose: To identify dosimetric advantages of the novel Dynamic WaveArc (DWA) technique for accelerated partial breast irradiation (APBI), compared with non-coplanar three-dimensional conformal radiotherapy (nc3D-CRT) and coplanar tangential volumetric modulated arc therapy (tVMAT) with dual arcs of 45–65°. Methods: Vero4DRT enables DWA by continuous gantry rotation and O-ring skewing with movement of the multi-leaf collimator. We compared the dose distributions of DWA, nc3D-CRT and tVMAT in 24 consecutive left-sided breast cancer patients treated with APBI (38.5 Gy in 10 fractions). The average doses and volumes to the planning target volume (PTV) and organs at risk, especially heart and left anterior descending artery (LAD) were compared among DWA, nc3D-CRT and tVMAT. Results: The doses and volumes to the PTVs did not differ significantly among the three plans. For the DWA plans, the mean dose to the heart was 0.2 ± 0.1 Gy, less than those of the nc3D-CRT and tVMAT plans. The D2% values of the planning organ at risk volume of the LAD were 9.3 ± 10.9%, 28.2 ± 31.9% and 20.3 ± 25.7% for DWA, nc3D-CRT and tVMAT, respectively. The V20Gy and V10Gy of the ipsilateral lung for the DWA plans were also significantly lower. Conclusions: DWA allowed to find a better compromise for OAR which overlapped with the PTV. Use of the DWA for APBI improved the dose distributions compared with those of nc3D-CRT and tVMAT.